Evaluation of Wiri Feeder Services on the Bratang - Pasar Turi Route - Atika Rahmadiarti; Dandy Patria; Ika Devy Pramudiana (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Efficient and integrated public transportation services are a strategic need in sustainable urban development. The Surabaya City Government through the Transportation Department initiated the Wira-Wiri Feeder service on the Bratang-Pasar Turi route (FD07) as a feeder mode that connects densely active areas in the east and west of the city. This study aims to evaluate the implementation and performance of FD07 services using the public policy evaluation framework of William N. Dunn (2003) which includes the dimensions of effectiveness, efficiency, adequacy, justice, responsiveness, and policy accuracy. The research uses a descriptive qualitative approach with data collection techniques through field observations, in-depth interviews, and documentation studies. The results of the study show that the implementation of FD07 services has been running according to operational procedures with an average of 651 passengers per day, supported by field supervision and the Surabaya Integrated Urban Transport System (SIUTS) digital system. However, there are still obstacles in the form of limited fleet numbers, non-professional drivers, limitations of senior mechanics, and inadequate system development budgets. Dunn's six-dimensional evaluation shows that the effectiveness and efficiency of the service are in the medium category, with the main challenges being the accuracy of schedules and the accessibility of bus stop facilities for people with disabilities. This study concludes that improving the quality of human resources, adding fleets, strengthening digital systems, and massive public socialization are strategic steps to realize effective, inclusive, and sustainable feeder services in the city of Surabaya.